Legalitas Pencatatan Perkawinan Beda Agama Pasca Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 - Antari, Putu Eva Ditayani; Adnyana, I Kadek Budiadinata Satriatama (Fundamental: Jurnal Ilmiah Hukum, 2024)
The trend of interfaith marriages is currently starting to be in demand in Indonesia. Data shows that until 2022 data on interfaith marriages totals 1425 brides. The presence of interfaith marriage polemics in society has resulted in the government through the Supreme Court issuing SEMA 2/2023 which prohibits the Court from accepting requests for interfaith marriages. Based on these problems, the author will examine the legality of interfaith marriages after the presence of SEMA 2/2023. Furthermore, in this study the authors raise the problem formulation 1. What is the basis for the publication of SEMA 2/2023? 2. How is the validity of interfaith marriages after the issuance of SEMA 2/2023? The purpose of this research namely. First, to find out the basis for the publication of SEMA 2/2023. Second, the validity of interfaith marriages after the issuance of SEMA 2/2023. In this study using the method of writing normative law, with several approaches such as the statutory approach, the case approach, and the conceptual approach. The collection of legal materials in this study used a library study technique. While the method of analysis of legal materials carried out is a juridical analytical descriptive method.